The Selective HDAC6 Inhibitor ACY-738 Impacts Memory and Disease Regulation in an Animal Model of Multiple Sclerosis - LoPresti, Patrizia (Frontiers in Neurology, 2019)
Multiple sclerosis (MS) is a complex disease characterized by autoimmune demyelination and progressive neurodegeneration. The pathogenetic mechanisms of the disease remain largely unknown. Changes in synaptic functions have been reported; however, the significance of such alterations in the disease course remains unclear. Furthermore, the functional consequences of targeting synapses are not well established. Synapses have key signaling elements, which regulate intracellular transport and overall neuronal health. Histone deacetylase (HDAC) 6 is a microtubule-associated deacetylase. The interaction between HDAC6 and microtubules is augmented with HDAC6 inhibitors. In this study, experimental autoimmune encephalomyelitis (EAE) mice, an animal model of MS, were treated on 9 and 10 days post-immunization (d.p.i.) with the HDAC6 inhibitor drug ACY-738 (20 mg/kg). Mice were then assessed using the cross-maze-test at 10 d.p.i., and the disease scores were recorded until 4 weeks post-immunization. We observed that ACY-738 delayed disease onset and reduced disease severity. Most importantly, it increased short-term memory in a manner sensitive to disease severity. We induced EAE disease with various amounts of myelin oligodendrocyte glycoprotein (MOG35-55). EAE mice receiving 100 g of MOG35-55 and treated with the drug had a statistically significant increase of short term-memory when these mice were compared with naïve mice. Additionally, EAE mice receiving 50 g MOG and treated with the drug had a statistically significant increase of short term-memory when these mice were compared with EAE mice without drug treatment. In contrast, the drug did not change short-term memory in EAE mice receiving 200 g of MOG35-55. As the drug increases short-term memory only with lower amounts of EAE-inducing reagents, we hypothesize that the inflammatory-demyelinating environment induced by higher amount of EAE-inducing reagents overpowers (at day 10 postimmunization) the synaptic molecules targeted by the drug. These studies pave the way for developing ACY-738-like compounds for MS patients and for using ACY-738 as a probe to elucidate disease-sensitive changes at the synapses occurring early in the disease course.